2012
DOI: 10.1007/s12155-012-9279-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies

Abstract: We obtained soil samples from geographically diverse switchgrass (Panicum virgatum L.) and sorghum (Sorghum bicolor L.) crop sites and from nearby reference grasslands and compared their edaphic properties,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Using Brightfield microscopy, Watrud et al . () found active bacterial biomass greater in switchgrass and grassland sites compared to sorghum, but no differences in active fungal biomass. A recent study by Liang et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Using Brightfield microscopy, Watrud et al . () found active bacterial biomass greater in switchgrass and grassland sites compared to sorghum, but no differences in active fungal biomass. A recent study by Liang et al .…”
Section: Discussionmentioning
confidence: 91%
“…There are few direct studies examining switchgrass SMB, and frequently they use different methods. Using Brightfield microscopy, Watrud et al (2013) found active bacterial biomass greater in switchgrass and grassland sites compared to sorghum, but no differences in active fungal biomass. A recent study by Liang et al (2012) found no significant difference between corn and switchgrass, but a significant increase under prairie or restored prairie in microbial lipid C concentration (a proxy for microbial biomass) in the 0-10 cm depth across 10 corn and 9 switchgrass sites in southern Wisconsin (averaging 10 years management).…”
Section: Switchgrass Increased Soil Aggregate Stability and Smb-cmentioning
confidence: 86%
“…Some studies in biomass cropping systems have not observed differences in soil microbial responses between perennial and annual crop types (Mao et al, 2011), while others have measured significant differences in microbial abundance, diversity and community structure between these cropping types (Liang et al, 2012;Morales et al, 2010;Watrud et al, 2013). Currently, we observed significantly higher nosZ gene copies in miscanthus soils compared to corn-soybean soils, illustrating a distinct effect of LUC from corn-soybean to miscanthus production on soil N cycling (Table 2).…”
Section: Bacterial Responses To Annual and Perennial Crops And Their mentioning
confidence: 57%
“…Quantifying soil P available to plants is challenging, especially if attempting to do this dynamically during a growing season. Typical chemical extraction methods (e.g., Bray, Olsen, or Mehlich III) quantify only a fraction of the inorganic P pool and are typically measured in top soils prior to planting 13 , 14 . Although the P concentration data obtained with these methods have been widely used in the literature to represent total P availability, they are not an accurate measure of P available for plant growth.…”
Section: Introductionmentioning
confidence: 99%